Conduction disturbances after surgical correction of ventricular septal defect by the atrial approach. - Hobbins, S M (1979)
Conduction disturbances have been documented after correction of ventricular septal defects by the ventricular route. Recently, repair of the ventricular septal defect has been through the right atrium to overcome damage to the conduction system and a right ventriculotomy. Thirty-nine children with ventricular septal defects under the age of 5 years were operated upon by the atrial route (group 1). The incidence of conduction disturbances in this group was compared with that occurring in 19 children of comparable age with a ventricular septal defect repaired via a right ventriculotomy (group 2). Complete right bundle-branch block developed in 13 of 39 children (33.3%) in group 1, compared with 15 of 19 children (78.9%) in group 2. This was a statistically significant reduction in complete right bundle-branch block in group 1. The incidence of left axis deviation occurring with complete right bundle-branch block was similarly statistically reduced. Transient complete heart block and arrhythmias were not statistically different in the two groups. The atrial approach to the repair of the ventricular septal defect significantly reduced the incidence of complete right bundle-branch block alone and occurring with left axis deviation.